Designing Cooperative Frameworks for Higher Education: The Structural Evaluation of the TIM-IGIS Prototype in Enhancing Preservice Teachers' Conceptual Learning Outcomes - Eky Setiawan Salo; Abdullah Pandang; Pattaufi (Jurnal Teknologi Pendidikan, 2026)
This study addresses the persistent pedagogical challenge in higher education where traditional, lecturer-centered instruction restricts student engagement and reduces conceptual learning outcomes. To mitigate this issue, this article presents the structural design, expert validation, and empirical evaluation of the Tim-based Interactive Game and Interpretation Strategy (TIM-IGIS) cooperative learning model prototype. Developed using the systematic framework of the ADDIE model, the TIM-IGIS prototype integrates five distinct phases: Initiative, Heterogeneous Groups, Gamified Engagement, Interpretation, and Summarization. The model was implemented using a single-group pretest posttest design with an intact educational cohort of 33 preservice teacher education students enrolled in the Elementary School Civics Learning Development course at Universitas Kristen Indonesia Toraja. Expert judgment via Aiken’s V established a high level of content and construct validity (V = 0.938), confirming the prototype’s alignment with cooperative principles. Field implementation demonstrated exceptional practicality, achieving a syntax implementation rate of 97.50% and highly active student engagement (M = 3.70). Empirically, the prototype significantly enhanced conceptual mastery, with the mean score rising from 63.03 to 81.76 (t(32) = 10.750, p < 0.001), yielding a substantial Cohen’s dz effect size of 1.871 and a moderate normalized gain (g = 0.502). These findings indicate that the TIM-IGIS prototype offers a robust, structurally balanced framework for promoting deep conceptual understanding and active collaboration in teacher training programs.